Homocysteine induces cytotoxicity and proliferation inhibition in neural stem cells via DNA methylation in vitro. (17th March 2014) - Lin, Ningning; Qin, Shanchun; Luo, Suhui; Cui, Shanshan; Huang, Guowei; Zhang, Xumei
<x xml:space="preserve">Abstract</x> Mild to moderate hyperhomocysteinemia has been implicated in neurodevelopmental disorders and neurodegenerative diseases in human studies. Although the molecular mechanisms underlying the effects of homocysteine (Hcy) neurotoxicity on the nervous system are not yet fully understood, inhibition of neural stem cell (NSC) proliferation and alterations in DNA methylation may be involved. The aim of the present study was to characterize the effects of Hcy on DNA methylation in NSCs, and to explore how Hcy‐induced changes in DNA methylation patterns affect NSC proliferation. We found that d, l‐Hcy (30–1000 μm) but not l‐cysteine inhibited cell proliferation and reduced levels of global DNA methylation in NSCs from neonatal rat hippocampus and increased cell injury. High levels of Hcy also induced an increase in S‐adenosylhomocysteine (SAH), a decrease in the ratio of S‐adenosylmethionine (SAM) to SAH, and a reduction in protein expression of the DNA methyltransferases DNMT1, DNMT3a and DNMT3b and their enzymatic activity. Moreover, the DNMT inhibitor zebularine reduced the global DNA methylation level and inhibited NSC proliferation. Our results suggest that alterations in DNA methylation may be an important mechanism by which high levels of Hcy inhibit NSC viability in vitro. Hcy‐induced DNA hypomethylation may be caused by a reduction in the DNMT activity which is regulated by the cellular concentrations of SAM and SAH, or their protein expression levels. Our results also suggest that Hcy may play a role in the pathogenesis of certain nervous system diseases via a molecular mechanism that involves negative regulation of NSC proliferation and alterations in DNA methylation.